Detection of 5 Kinds of Genes Related to Plasmid-Mediated Quinolone Resistance in Four Species of Nonfermenting Bacteria with 2 Drug Resistant Phenotypes - De-Song Ming; Qing-Qing Chen; Xiao-Ting Chen (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. This study aimed to detect 5 kinds of genes related to plasmid-mediated quinolone resistance in four species of nonfermenting bacteria with 2 drug resistance phenotypes (multidrug resistance and pandrug resistance), which were Acinetobacter baumannii (Ab), Pseudomonas aeruginosa (Pa), Stenotrophomonas maltophilia (Sm), and Elizabethkingia meningoseptica (Em). Methods. The Phoenix NMIC/ID-109 panel and API 20NE panel were applied to 19 isolated strains, including 6 Ab strains (2 strains with multidrug resistance and 4 strains with pandrug resistance), 6 Pa strains (3 strains with multidrug resistance and 3 strains with pandrug resistance), 4 Sm strains (2 strains with multidrug resistance and 2 strains with pandrug resistance), and 3 Cm strains (2 strains with multidrug resistance and 1 strain with pandrug resistance). After strain identification and drug susceptibility test, PCR was applied to detect 5 genes related to plasmid-mediated quinolone resistance. The genes detected were quinolone resistance A (qnrA), aminoglycoside acetyltransferase ciprofloxacin resistance variant, acc(6′)-Ib-cr, and 3 integrons (intI1, intI2, and intI3). The amplified products were analyzed by 1% agarose gel electrophoresis and sequenced. Sequence alignment was carried out using the bioinformatics technique. Results. Of 19 strains tested, 8 strains carried acc(6′)-Ib-cr and 6 of them were of pandrug resistance phenotype (3 Ab strains, 2 Pa strains, and 1 Sm strain). The carrying rate of acc(6′)-Ib-cr was 60.0% for strains of pandrug resistance (6/10). Two strains were of multidrug resistance (1 Ab strain and 1 Pa strain), and the carrying rate of acc(6′)-Ib-cr was 22.0% (2/9). The carrying rate was significantly different between strains of multidrug resistance and pandrug resistance (P<0.05). The class 1 integron was detected in 11 strains, among which 6 strains were of pandrug resistance (3 Ab strains, 2 Pa strains, and 1 Sm strain). The carrying rate of the class 1 integron was 60.0% (6/10). Five strains were of multidrug resistance (3 Pa strains, 1 Ab strain, and 1 Em strain), and the carrying rate was 55.6% (5/9). The carrying rate of the class 1 integron was not significantly different between strains of multidrug resistance and pandrug resistance (P>0.05). Both acc(6′)-Ib-cr and intI1 were detected in 6 strains, which were negative for qnrA, intI2, and intI3. Conclusion. Quinolone resistance of isolated strains was related to acc(6′)-Ib-cr and intI1 but not to qnrA, intI2, or intI3. The carrying rate of acc(6′)-Ib-cr among the strains of pandrug resistance was much higher than that among the strains of multidrug resistance. But, the strains of two drug resistant phenotypes were not significantly different in the carrying rate of intI1. The detection rates of the two genes were high and similar in Ab and Pa strains. 1 Em strain carried the class 1 integron.